Παράγοντες έγερσης του ηθικού αδιεξόδου στη νοσηλευτική και επιπτώσεις του στην πρακτική - Χαϊκάλη, Στυλιανή; Παπαθανάσογλου, Ελισάβετ; Lemonidou, Chryssoula; Πατηράκη, Ελισάβετ; Γιαννακοπούλου, Μαργαρίτα (My University, 2011)
Introduction. Moral distress is a phenomenon which is usually experienced by health professionals. It occurs when they know the ethically appropriate course of action to take, but are unable to carry it out because of obstacles existence (internal or external). Despite its spread, most nurses don't know the factors generating moral distress Aim. The purpose of this study was to investigate the generating factors of moral distress as well as its effects in practice. Method. A systematic review of research articles published from 1999-2010 in Medline, Embase, Cohrane Library, Cinahl and Google was conducted. Articles that investigated different aspects of moral distress, or those which were focused in pediatric units were excluded. Inclusion criteria were the english language and the methodological completeness. Forty-five articles were included in the sample. Results. According to our results, it seems that the most important factors that generate moral distress are: futile care, low nurse/physician collaboration, patients' deception, inadequate staffing, ethical dilemmas, lack of autonomy, competing obligations. As a result of moral distress nurses experience psychological problems. Other effects involve quality of patient care, job satisfaction and turnover intention. Conclusions. The most important coping strategies in order to mitigate the effects of moral distress are: increase staffing levels, improve communication between nurses and physicians, create positive ethical environment.
Generating factors of moral distress in nursing and its effects in practice